The Parliament of Canada - Franks, C. E. S. (Book collections on Project MUSE., 1987)
More MPs resign voluntarily in Canada than their counterparts in either Britain or the United States. A recent Gallup poll found that the majority of Canadians have little to no interest in Parliament. Western Canadians are agitating for the establishment of a 3-E Senate: elected, equal, effective. In this provocative study C.E.S Franks explores the nature of Canada's parliamentary system and the roots of current dissatisfaction with its institutions. He compares the demands made on MPs with their essentially amateur abilities to govern. He relates the institution of Parliament to broader questions about political parties in general, and considers the relationship of Parliament to the executive branch in policy-making and accountability.